(untitled) (World Bulletin of Public Health, 2025)
Dental-origin inflammatory bone diseases represent a significant clinical challenge in contemporary oral and maxillofacial surgery, encompassing a spectrum of pathological conditions ranging from localized osteitis to severe osteomyelitis with systemic complications. These conditions arise from the spread of odontogenic infections through anatomical pathways, leading to progressive inflammatory and destructive processes within the maxillary and mandibular bone structures.